2008
DOI: 10.1155/2008/219672
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatisSerology in Women with and without Ovarian Cancer

Abstract: Pelvic inflammation has been implicated in the genesis of ovarian cancer. We conducted serologic measurements of Chlamydia trachomatis antibodies as a surrogate marker of chlamydial pelvic inflammatory disease. Women with ovarian cancer (n = 521) and population-based controls (n = 766) were tested. IgG antibodies to serovar D of chlamydia elementary bodies (EBs) were detected using an ELISA assay. The odds of having ovarian cancer among women with the highest titers (≥0.40 OD units) were 0.6 (95% CI 0.4–0.9). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 10 publications
(15 reference statements)
3
23
0
Order By: Relevance
“…In the analysis considering "high" and "low" positive antibody levels to C. trachomatis cHSP60-1 antibodies and EOC risk, women with high positive antibody levels had higher risk of EOC only among women <60 at blood collection (P het = 0.04; <60 years, Our findings of positive associations between select C. trachomatis antibodies and EOC risk are in line with the results of three previous studies 18,19,25 ; however, others have observed no association. 20,22,24 Previous studies have predominantly analyzed ovarian cancer as a single disease, with small sample size precluding analyses by subtype beyond serous vs nonserous disease. [18][19][20]22,24,25 In the current study, we provide a detailed investigation by histotype, observing suggestive heterogeneity by tumor histology.…”
Section: Sensitivity and Subgroup Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the analysis considering "high" and "low" positive antibody levels to C. trachomatis cHSP60-1 antibodies and EOC risk, women with high positive antibody levels had higher risk of EOC only among women <60 at blood collection (P het = 0.04; <60 years, Our findings of positive associations between select C. trachomatis antibodies and EOC risk are in line with the results of three previous studies 18,19,25 ; however, others have observed no association. 20,22,24 Previous studies have predominantly analyzed ovarian cancer as a single disease, with small sample size precluding analyses by subtype beyond serous vs nonserous disease. [18][19][20]22,24,25 In the current study, we provide a detailed investigation by histotype, observing suggestive heterogeneity by tumor histology.…”
Section: Sensitivity and Subgroup Analysesmentioning
confidence: 99%
“…20,22,24 Previous studies have predominantly analyzed ovarian cancer as a single disease, with small sample size precluding analyses by subtype beyond serous vs nonserous disease. [18][19][20]22,24,25 In the current study, we provide a detailed investigation by histotype, observing suggestive heterogeneity by tumor histology. Pgp3 serology indicating current or past infection with C. trachomatis was not associated with EOC risk overall in contrast to two recent studies, 18,25 but was associated with significantly higher risk of mucinous EOC; this has not previously been described.…”
Section: Sensitivity and Subgroup Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several studies, which attempted to find an association between C. trachomatis and ovarian cancer (Idahl et al, 2010;Ness et al, 2003;Ness et al, 2008;Shanmughapriya et al, 2012). However, these studies employ analysis of IgG antibodies in patients or bacterial genetic material in the tumour samples.…”
Section: Downregulation Of P53 Duringmentioning
confidence: 99%
“…Ness and colleagues [59] reported a significant difference in IgG antibody titers against Ctr elementary bodies and heat shock proteins (CHSP) in the serum of ovarian cancer patients compared to the control group, but failed to validate the finding in a larger, population-based group [60]. In a more recent patient cohort analyzed by Idahl et al .…”
Section: The Tumorigenic Effects Of Oxidative Stress and Inflammatmentioning
confidence: 99%